2022
DOI: 10.3389/fmicb.2022.858064
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryogenesis: The Rise of an Emergent Superorganism

Abstract: Although it is widely taught that all modern life descended via modification from a last universal common ancestor (LUCA), this dominant paradigm is yet to provide a generally accepted explanation for the chasm in design between prokaryotic and eukaryotic cells. Counter to this dominant paradigm, the viral eukaryogenesis (VE) hypothesis proposes that the eukaryotes originated as an emergent superorganism and thus did not evolve from LUCA via descent with incremental modification. According to the VE hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 90 publications
1
8
0
Order By: Relevance
“…With the exception of Polε, our results show that the genes required for processive DNA replication and transcription are primarily viral-derived (Figure 3A), while other key processes in eukaryotes such as translation, the ubiquitin-proteasome system, and endomembrane trafficking have been shown to have primarily archaeal origins 2,3 (Figure 3A). Although it is challenging to disentangle the exact scenario of gene transfer that led to this pattern, it is striking to note that our results are remarkably consistent with a model of viral eukaryogenesis previously put forward by Bell 26 . In this model, the eukaryotic nucleus is derived from a membrane enclosed “virus factory” (VF) that formed during a chronic infection (Figure 3B).…”
Section: Main Textsupporting
confidence: 88%
“…With the exception of Polε, our results show that the genes required for processive DNA replication and transcription are primarily viral-derived (Figure 3A), while other key processes in eukaryotes such as translation, the ubiquitin-proteasome system, and endomembrane trafficking have been shown to have primarily archaeal origins 2,3 (Figure 3A). Although it is challenging to disentangle the exact scenario of gene transfer that led to this pattern, it is striking to note that our results are remarkably consistent with a model of viral eukaryogenesis previously put forward by Bell 26 . In this model, the eukaryotic nucleus is derived from a membrane enclosed “virus factory” (VF) that formed during a chronic infection (Figure 3B).…”
Section: Main Textsupporting
confidence: 88%
“…By analyzing the amino acid frequencies in the eukaryotic IDR region 26 , they are surprisingly similar with LLPS sequences 8 . Given that the arise of eukaryotic organism is an early event in evolution (estimated to be at least 2.7 billion years ago 60 ), if the equipment of LLPS was harvested by the cell not much later than the event, LLPS systems and PPI networks would have long history of coordinated coevolution 28 . For the capability of LLPS on the spatiotemporal regulation of protein distribution and its proteome-wide spreading, PPI and LLPS networks are deeply engaged and have an intimate relationship.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have demonstrated that modern eukaryotic and viral genomes are a product of deeply intertwined coevolution. Although the details of eukaryogenesis remain enigmatic, several scenarios in which giant viruses play central roles have been postulated (Takemura 2020 , Bell 2022 ).…”
Section: Main Textmentioning
confidence: 99%